The promise of digital healthcare technologies - Yeung, Andy Wai Kan; Torkamani, Ali; Butte, Atul J.; Glicksberg, Benjamin S.; Schuller, Björn; Rodriguez, Blanca; Ting, Daniel S. W.; Bates, David; Schaden, Eva; Peng, Hanchuan; Willschke, Harald; van der Laak, Jeroen; et al. (Frontiers in Public Health, 2023)
Digital health technologies have been in use for many years in a wide spectrum of healthcare scenarios. This narrative review outlines the current use and the future strategies and significance of digital health technologies in modern healthcare applications. It covers the current state of the scientific field (delineating major strengths, limitations, and applications) and envisions the future impact of relevant emerging key technologies. Furthermore, we attempt to provide recommendations for innovative approaches that would accelerate and benefit the research, translation and utilization of digital health technologies.